The influence of return investment on enterprise financing cost - Zhang, Gaohan (International Journal of Global Economics and Management, 2023)
In this paper, the influence of return investment on the financing cost of enterprises is deeply studied, and several key factors related to it are discussed. Firstly, from the perspective of regional differences, this paper analyzes the influence of financial market characteristics, regulatory environment and tax policies in different regions on corporate financing decisions. It is found that fully considering regional differences will help enterprises to formulate financing strategies for return investment, reduce costs and improve efficiency. Secondly, by digging deep into the interaction between enterprise strategy and financing, it reveals how enterprise strategic choice shapes financing structure and its influence on financing cost. The choice of different strategies may lead to the difference of financing demand, and the synergy between the long-term stability strategy and financing cost highlights the complex relationship. Furthermore, from the perspective of global financial market, this paper discusses how enterprises can reduce costs through flexible financing by taking advantage of the opportunities of global financial market. The in-depth analysis of the factors of global financial market, such as exchange rate risk, interest rate difference and capital flow, enables enterprises to better grasp the financing opportunities on a global scale. Finally, suggestions for future research are put forward, including in-depth study of regional and industry differences, attention to the impact of emerging technologies on financing, and more interdisciplinary research methods.